The city she was : poems - Giménez Smith, Carmen, 1971- (Mountain west poetry series., 2011)
""When you open this book, expect serious role-playing and syntactic tap dancing. The City She Was presents a world that brings 'the horizon line into your lexicon' and a poet's muse ('The Endangered You') is lent to a friend and returned 'a little more frayed.' Giménez Smith muddles and enchants with her many masks, leaving the ground a little less stable under our feet."" -Matthea Harvey, author of Modern Life, Sad Little Breathing Machine, and Pity the Bathtub Its Forced Embrace of the Human Form.